Answer:
S3 = 39
Explanation:
* an = 3(3)^(n-1) is a geometric sequence
* The general rule of the geometric sequence is:
an = a(r)^(n-1)
Where:
a is the first term
r is the common difference between each consecutive terms
n is the position of the term in the sequence
The rules means:
- a1 = a , a2 = ar , a3 = ar² , a4 = ar³ , ........................
∵ an = 3(3)^(n-1)
∴ a = 3 and r = 3
∴ a1 = 3
∴ a2 = 3(3) = 9
∴ a3 = 3(3)² = 27
* S3 = a1 + a2 + a3
∴ S3 = 3 + 9 + 27 = 39
Note:
We can use the rule of the sum:
Sn = a(1 - r^n)/(1 - r)
S3 = 3(1 - 3³)/1 - 3 = 3(1 - 27)/-2 = 3(-26)/-2 =3(13) = 39